Os iguais, desiguais: entendendo o consumo cultural pelas classes populares - Müller, Caroline Regina (Universidade do Vale do Rio dos Sinos, 2014)
At the end of the year 2013 goes into effect in Brazil the “culture voucher” law, which guarantees a monthly benefit for workers earning less than five minimum wages. This voucher is initially destined to people in popular classes, assuming that they do not actively participate in cultural events. Thus, taking the theory of Bourdieu (1979) as the basis and the law as the motivator of questions, this study sought to understand how the popular classes relate to the legitimate taste, i.e. to comprehend how these people accept what is imposed as genuine culture by the elite. From an interpretive approach and a combination of multiple qualitative techniques to collect data through in-depth interviews, as well as a participant observation and interviews with images and design thinking, we sought to answer the study's objective. It is possible to observe that young people from lower classes are quite heterogeneous in their tastes. Thus, from the heterogeneity and the similarities they establish bridges or walls with others. In the field it was revealed that teenagers are subdivided into three groups of consumption practices: local, global and outliers. Each of these groups has cultural products which characterize them. Moreover, the culture consumed by the popular classes is one that is easily accessible, i.e. mass culture. Due to the heterogeneity of individuals in this class and the singularities of cultural products consumption, the government should take into account the characteristics of the popular classes’ citizens so the promotion of public policies associated to the cultural consumption has the intended effect in the decrease of inequalities.
Keywords: Cultura e consumo; Capital cultural; Gosto legítimo; Produtos culturais; Culture and consumption; Cultural capital; Legitimate taste; Cultural products; ACCNPQ::Ciências Sociais Aplicadas::Administração